Decoding the Formation and Elimination Mechanism of Ethyl Carbamate in Strong-Aroma Baijiu - Liqiang Zhang; Yue Qiu; Yongqing Zhang; Yintao Jia; Baoguo Sun; Wei Dong (Foods)
In the present study, changes in the physicochemical indices, ethyl carbamate (EC) precursor and EC contents, and microbial communities of fermented grains under different fermentation patterns during strong-aroma Baijiu (SAB) fermentation and changes in EC precursor and EC contents during distillation were investigated to study EC formation during these processes. In detail, the amounts of sorghum added in protocols C and D were half those added in protocols A and B (the normal SAB-producing technology). When fermented for about 30 to 35 days, the fermented grains of protocols A and C were, respectively, remixed with Daqu and second-distilled SAB (so-called “Huijiu jiaqu”, HJJQ) and fermented for about 30 to 40 days. The results showed that the acidities of the final fermented grains of protocols A (2.43 ± 0.09 mmol/10 g) and C (3.18 ± 0.08 mmol/10 g) were lower than those of protocols B (3.71 ± 0.07 mmol/10 g) and D (4.66 ± 0.10 mmol/10 g), while the alcohol contents in the final fermented grains of protocols A (18.33 ± 0.76%) and C (15.33 ± 1.08%) were higher than those of protocols B (5.10 ± 0.85%) and D (1.85 ± 0.62%). No significant differences were observed in the other physicochemical indices among the samples. The HJJQ operation significantly increases the alcohol content and reduces the acidity of the fermented grains but has little influence on the other physicochemical indices during SAB fermentation. Excluding the influence of the HJJQ operation and a half input of sorghum on the EC precursor and EC contents for the fermented grains of protocol B, the linear relationships between the EC content and alcohol (R2: 0.4465), citrulline (R2: 0.6962), urea (R2: 0.4705), and HCN (R2: 0.6324) contents were good (all the confidence levels were at 0.05), indicating that these compounds were the dominant EC precursors during SAB fermentation. HJJQ also facilitated the reaction between alcohol and other EC precursors, decreasing EC precursor content and increasing the EC content. KEGG pathway analysis demonstrated that EC precursors were mainly synthesized by alcohol and arginine metabolism. HCN (R2: 0.3875 to 0.8198) and alcohol (R2: 0.4642 to 0.8423) were the dominant EC precursors during SAB distillation. Overall, the HJJQ operation, especially in protocol C, could significantly reduce the content of EC in base SAB, and the base SAB obtained was of good quality. This, therefore, may be an alternative and effective way to reduce the EC content in base Baijiu.